Différance in the French Versions of the Synoptic: A Case for Intralingua Translation - Gbadegesin Olusegun Adegboye; Olusanya Philp Siji (LingLit Journal Scientific Journal for Linguistics and Literature, 2023)
This study centers on the intralingua overview of différance in the three French versions of selected verses from the gospels of Jesus Christ as recorded by Mathew, Mark, Luke and John. The objectives of this study are to: describe what différance is in translation studies; examine the meaningfulness of the meaning accorded the selected verses across the three versions of the French Bible to the designated audience; explain variations in the intralingua rendering of the synoptic; analyze the spiritual impression the different meanings generated by the chosen Bible versions could possibly have on the readers; and expound the language movement of French and its strength in communicating the intent of the gospel to the target audience. Skopos theory by Reiss and Vermeer (1984) is adopted to x-ray the purpose of the translation strategy used by each of the three versions of the Bible in French. Seven statements of Jesus Christ across the four gospels were quoted. The verses were compared and the différance examined. Implication of the meaning transfer by each of the versions is viewed in the spirit of intralingua translation and its attending spiritual intelligibility to the target readers. The study finds out that: every version of the French Bible considered makes effort to convey Jesus’ messages in a way it feels the reader should understand; while some versions pay premium to conventional language structure to translate, other shows concern for content and “sacred” transfer of the divine words; symbols used by Jesus Christ are preserved in the three versions but the spiritual impression wanes in favor of language structure in some versions. The study concludes that intralingua approach to translating the Scriptures is to satisfy different categories of readers and différance underlines the essence of variations in communicating the gospel to the readers of the Bible in French.